Extreme Natural Events Mitigation: An Analysis of the National Disaster Funds in Latin America - Szlafsztein, Claudio Fabian (Frontiers in Climate, 2020)
This paper review, compare, and analyze the legal and institutional framework of Latin American government insurance systems for disaster risk. Data and information are obtained through an intense examination of disasters database, the scientific literature and legal framework of administrative and operational procedures, and mainly, sources of financial funds related to disaster risk management. The results demonstrate that all countries, with the exception of Ecuador and Chile, legally establish some form of fund by their own legislation and regulation, as a total or partial form of financing the management of natural disasters, particularly those classified as post-disaster recuperation and reconstruction practices. North and Central American countries have more complex and well-structured funds, presumably based on their history of natural disasters and high social vulnerability. The funds are composed of initial values defined by law, annual contributions of general budgets, donations, and the financial gains of resources deposited into bank accounts. The paper concludes that the unavailability of required resources in an emergency situation has led Latin American countries to choose disaster funds as a primary disaster risk management financing strategy. However, the uncertainty of natural disaster occurrence is one of the main obstacles to the use of public financial resources in prevention and preparedness strategies and actions, increasing even more with the inclusion of climate change uncertainties.